ECONOMIC AND FINANCIAL INTEGRATION IN EMERGING MARKETS - E. Theodoropoulos, Theodore; Vojinovic, Borut (Economic Annals, 2005)
This paper extends to test if the same short-run increase in cyclical volatility arising from financial integration is observed in this specific sample of “emerging markets”. This work finds signs that, contrary to other emerging markets, this does not happen: for the future Member States, financial integration, similarly to the outcome observed in mature market economies, reduces cyclical volatility both in the short and in the long run. Weak indications are found that this may happen partially due to the anchoring of expectations provided by the EU Accession, and to the more robust institutional framework imposed by this process onto the countries in question.